Kerajaan Allah dalam Injil Lukas - Riky Riky; Vanesa Seftilavika; Gefriyani Wulan Dari; Sarmauli Sarmauli (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
The Gospel of Luke places special emphasis on the concept of the Kingdom of God as the core of the preaching of Jesus Christ. In Luke's understanding, the Kingdom of God is not merely an eschatological reality that will come in the future, but also a spiritual reality that has been present through the work, teachings, and ministry of Jesus. This study aims to explore in depth the meaning, characteristics, and implications of the Kingdom of God as presented in the Gospel of Luke. The research method used is a qualitative approach with a literature study of biblical texts and relevant theological references. The results of the study show that the Kingdom of God in the Gospel of Luke has several important aspects, namely being theocentric, dynamic, messianic, and closely related to salvation. The Kingdom of God is present in the ministry of Jesus and is marked by real actions such as forgiveness of sins, healing, and preaching to marginalized groups. The implications of this study emphasize that a correct understanding of the Kingdom of God will bring about radical changes in life and require repentance, faith, and active involvement in the preaching of the Gospel. Thus, the concept of the Kingdom of God in the Gospel of Luke has strong relevance to the lives of believers today.